Preparation of CCF/MWCNT-OH/Graphite/Resin Composite Bipolar Plates Using Bi-Directional Interfacial Modification and Study of Their Performance Improvement and the Mechanism of Their Interfacial Bonding Improvement - Wenkai Li; Haodong Zeng; Zhiyong Xie (C)
Composite bipolar plates are a new class of material bipolar plates for PEMFCs. However, their application is limited by problems such as the difficulty of balancing their strength/conductivity properties. In this paper, by using surface-modified carboxylated short-cut carbon fibers and hydroxylated carbon nanotubes as well as PI resin, the interfacial bonding between the carbon-based filler and the resin is effectively improved under the premise of ensuring electrical conductivity, which enhances the flexural strength. The effect of the surface modification of the filler on the interfacial bonding between the filler and the PI resin is thoroughly investigated through molecular dynamics simulations. The mechanism for this improved bonding was also studied. Through the surface modification of the filler, the composite bipolar plates possessed a flexural strength of 49.06 MPa and a planar conductivity of 228.52 S/cm with the addition of 6% MWCNT-OH as well as 12% CCFs, which has the potential to be an optional substrate for composite bipolar plates.